2018
DOI: 10.1007/s00277-018-3468-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of front line relative dose intensity for methotrexate and comorbidities in immunocompetent elderly patients with primary central nervous system lymphoma

Abstract: Primary central nervous system lymphomas (PCNSL) are non-Hodgkin lymphomas strictly localized to the CNS, occurring mainly in elderly patients with comorbidities. Current treatment in fit patients relies on high-dose methotrexate and high-dose cytarabine. The aim of this study was to evaluate the efficacy and feasibility of this treatment in elderly patients and to assess potential prognostic factors associated with survival. We conducted a retrospective study in two centers between January 2008 and September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 46 publications
0
27
1
Order By: Relevance
“…Survival outcomes for older patients remain poor and have been the focus of several recent trials. [10][11]13,16 Outcomes of the less intensive group in our study (two-year PFS 11%) were inferior to those of recent retrospective studies, one of patients >60 years (two-year PFS of 52%) 16 and another with a subgroup analysis of patient >60 years (median PFS of 39 months). 17 These study populations had a better ECOG and a younger age than our less intensive cohort, potentially explaining this finding.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Survival outcomes for older patients remain poor and have been the focus of several recent trials. [10][11]13,16 Outcomes of the less intensive group in our study (two-year PFS 11%) were inferior to those of recent retrospective studies, one of patients >60 years (two-year PFS of 52%) 16 and another with a subgroup analysis of patient >60 years (median PFS of 39 months). 17 These study populations had a better ECOG and a younger age than our less intensive cohort, potentially explaining this finding.…”
Section: Discussioncontrasting
confidence: 90%
“…Data from the HOVON105/ALLG NHL 24 prospective trial did not demonstrate benefit of rituximab in terms of event‐free survival (EFS) when added to the MBVP induction regimen (one‐year EFS 52% vs. 49%) 22 although a study level meta‐analysis of pooled data from IELSG32 and HOVON105 confirmed a PFS benefit 23 . Notwithstanding, most centres now routinely include rituximab within PCNSL protocols and our study supports this approach 5,16‐17,24,25 …”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In total we identified five completed [32,42,43,45,49,50] and one ongoing RCT [29], 26 prospective studies (two with control [67,69], 24 single arm studies [31,[55][56][57][58][59][60][61][62][63][64][65][66]68,[70][71][72][73][74][75][76][77][78][79] and 24 retrospective studies (with or without control) [17,30,37,45,[80][81][82][83][84][85][86][87][88][89][90][91][92]…”
Section: Discussionmentioning
confidence: 99%